2022
DOI: 10.3389/fnhum.2022.814204
|View full text |Cite
|
Sign up to set email alerts
|

Anodal Transcranial Direct Current Stimulation Over Prefrontal Cortex Slows Sequence Learning in Older Adults

Abstract: Aging is associated with declines in sensorimotor function. Several studies have demonstrated that transcranial direct current stimulation (tDCS), a form of non-invasive brain stimulation, can be combined with training to mitigate age-related cognitive and motor declines. However, in some cases, the application of tDCS disrupts performance and learning. Here, we applied anodal tDCS either over the left prefrontal cortex (PFC), right PFC, supplementary motor complex (SMC), the left M1, or in a sham condition wh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 86 publications
0
1
0
Order By: Relevance
“…Close to our task, Raw et al (2016) did not report any evidence of a-tDCS effect (over left M1, 1,5 mA, 30 min) on explicit MSL by PP in different groups of age. In older adults, Greeley et al (2022) did not show any advantage of two sessions of PP of a discrete sequence production task combined with a-tDCS (over left M1, 2 mA, 20 min) on MSL, compared to sham-tDCS. Puri et al (2021) even showed that a-tDCS applied over right M1 (1.5 mA, 25 min) during a serial reaction time task altered subsequent performance, when assessed after a 24 h consolidation phase.…”
Section: Anodal Tdcsmentioning
confidence: 65%
“…Close to our task, Raw et al (2016) did not report any evidence of a-tDCS effect (over left M1, 1,5 mA, 30 min) on explicit MSL by PP in different groups of age. In older adults, Greeley et al (2022) did not show any advantage of two sessions of PP of a discrete sequence production task combined with a-tDCS (over left M1, 2 mA, 20 min) on MSL, compared to sham-tDCS. Puri et al (2021) even showed that a-tDCS applied over right M1 (1.5 mA, 25 min) during a serial reaction time task altered subsequent performance, when assessed after a 24 h consolidation phase.…”
Section: Anodal Tdcsmentioning
confidence: 65%
“…This explains the gradual fastening of the slow concatenation responses with extensive practice (Kennerley et al, 2004 ; Popp et al, 2020 ; Ramkumar et al, 2016 ; Verstynen et al, 2012 ; Verwey et al, 2022b ). Such association development may also explain the increase in average segment length across participants groups after hundreds or thousands of practice trials (Acuna et al, 2014 ; Greeley et al, 2020 , 2022 ; Ruitenberg et al, 2012a , b ; Wymbs et al, 2012 ).…”
Section: Reviewing Dsp Task Resultsmentioning
confidence: 99%
“…In addition to unveiling the underlying processing mechanisms, the DSP task has been used to address the effectiveness of procedures to boost motor sequence learning, like using mental practice (Sobierajewicz et al, 2016 ), and increasing contextual interference by randomly varying alternative sequences in a single block of trials (Random Practice, or RP), instead of practicing different sequences in separate blocks (Blocked Practice, or BP) 3 (Cross et al, 2007 ; Immink & Wright, 1998 ; Kim et al, 2018 ; Lin et al, 2012 , 2016 ; Verwey et al, 2022b ). In addition, DSP studies explored the learning benefits of noninvasive stimulation of brain areas like M1 and prefrontal areas using transcranial magnetic brain stimulation (TMS; Cohen et al, 2009 ; Kennerley et al, 2004 ; Ruitenberg et al, 2014 ; Verwey et al, 2022a ) and transcranial direct current stimulation (tDCS; Greeley et al, 2020 , 2022 ; Kim et al, 2020 , 2021 ; Kim & Wright, 2020 ; Sobierajewicz et al, 2019 ; Waters-Metenier et al, 2014 ).…”
Section: The Discrete Sequence Production (Dsp) Taskmentioning
confidence: 99%